Carrot and carotene and multiple health outcomes: an umbrella review of the evidence. (17th January 2023) - Yi, Xianyanling; Li, Jin; Liao, Dazhou; Peng, Ge; Zheng, Xiaonan; Xu, Hang; Zhang, Tianyi; Ai, Jianzhong
Abstract: In recent years, the benefits of carrots and carotene in different areas of health have been examined. The purpose of this umbrella review was to identify the associations between carrots and carotene and multiple health outcomes. The review considered evidence from meta‐analyses of interventional and observational studies of carrots and carotene and any health outcome. We comprehensively searched Web of Science, PubMed, and Embase. For each association, we estimated the summary effect size using random and fixed effects models and the 95% confidence interval. A total of 1329 studies were searched, and 30 meta‐analyses with 26 health outcomes were identified that met the eligibility criteria. Carrot intake was associated with a lower risk of multiple cancer outcomes including breast cancer, lung cancer, pancreatic cancer, gastric cancer, urothelial cancer, and prostate cancer. Carotene intake was associated with a lower risk of fracture, age‐related cataract, sunburn, Alzheimer's disease, breast cancer, lung cancer, pancreatic cancer, gastric cancer, esophageal cancer, prostate cancer, and head and neck cancer (HNC). Serum carotene was inversely associated with all‐cause mortality, breast cancer, and lung cancer. Our study revealed that carrot or carotene intake could reduce the risk of various negative health outcomes. © 2023 Society of Chemical Industry.